Life-course implications of US public policies - Wilmoth, Janet M. (Janet May); London, Andrew S. (New York : Routledge Taylor & Francis Group, 2021)
"Public policies are often narrowly focused and targeted legislative or regulatory guidelines. In Current Debates in Aging and the Life Course: Public Policy, the authors encourage others to systematically consider the influence of policies and programs on lives, aging, and the life course, and how the consequences may vary by race/ethnicity, sexual orientation, ability, and social class. The volume aims to foster an appreciation of how policy influences connect and condition the life course. Essays examine issues relating to cumulative Dis/Advantage, crime and nutrition, amongst other issues, and demonstrate how the principles of the life-course perspective and cumulative inequality theory can be used to re-shape contemporary public policy debates. Current Debates in Aging and the Life Course will be a great aid to students of sociology, social work, and, and public policy, as well as policy makers, think tanks, and lobbyists, who are concerned with age-based policy"--
OCLC-licensed vendor bibliographic record.
Keywords: Aging -- United States; Aging -- Social aspects; Public administration -- United States; Older people -- Care; SOCIAL SCIENCE / Gerontology; SOCIAL SCIENCE / Sociology / General